CORROSION INHIBITION OF LOW CARBON STEEL IN SIMULATED WASTEWATER FROM PETROLEUM INDUSTRY - CHELARU, Julieta Daniela; AYLAKOV, Dovran; MUREŞAN, Liana Maria (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The corrosion inhibition efficiency of three commercial inhibitors on low carbon steel was investigated by electrochemical methods (EIS and polarization curves). The efficiency of corrosion inhibitors was tested at different concentrations. Corrosion tests were carried out in a solution simulating a saline wastewater from petroleum industry (pH = 3) in order to find the best inhibitor for the protection of steel pipelines.